Systemic Deficiency of PTEN Accelerates Breast Cancer Growth and Metastasis - Chen, Jing; Sun, Jingjing; Wang, Qunfeng; Du, Yanze; Cheng, Jie; Yi, Juan; Xie, Bei; Jin, Suya; Chen, Gang; Wang, Lina; Wang, Xiaoyuan; Wei, Hulai (Frontiers in Oncology, 2022)
Mutation or loss of the tumor suppressor gene PTEN or its functional status in tumor stromal cells may affect tumor occurrence, development, invasion, and metastasis, in which, however, the role of overall low PTEN expression, mutation, or deletion in the tumor-bearing host has rarely been reported. Breast cancer is a common highly invasive metastatic tumor. We therefore treated mouse breast cancer 4T1 cells with the specific PTEN inhibitor VO-OHpic to study the effects of PTEN suppression or deletion on malignant behavior in vivo and in vitro. VO-OHpic effectively inhibited PTEN gene/protein expression in 4T1 cells, accelerated cell proliferation, and enhanced cell migration and invasion. We also transplanted 4T1 cells with VO-OHpic-inhibited PTEN into mice to create orthotopic and metastatic breast cancer models. The proliferation of 4T1 cells in mouse mammary gland was increased and distant metastasis was enhanced, with metastatic foci in the lung, liver, and intestinal tract. In addition, injection of mice with VO-OHpic to inhibit PTEN in the overall microenvironment accelerated the proliferation of transplanted 4T1 cells and enhanced distant metastasis and the formation of metastatic tumors. Metastatic foci formed in the lung, liver, intestine, thymus, and brain, and PTEN levels in the organ/tissues were negatively associated with the formation of metastatic foci. Similarly, inoculation of PTEN-deficient 4T1 cells into systemic PTEN-inhibited mice further enhanced the orthotopic growth and distant metastasis of 4T1 breast cancer. VO-OHpic inhibition of PTEN in 4T1 cells was also associated with significantly increased phosphorylation of Akt and phosphoinositide 3-kinase (PI3K), suggesting that inhibition of PTEN could activate the PI3K-Akt pathway, as a key signaling pathway regulating cell proliferation and death. These results confirmed that functional loss or deletion of the tumor suppressor gene PTEN significantly enhanced the proliferation, invasion, and metastasis of 4T1 cells. Systemic decrease or deletion of PTEN in the organism or organ/tissue microenvironment was conducive to the proliferation of breast cancer cells in situ and distant metastasis. These results suggest that, as well the PTEN in cancer cells the systemic microenvironment PTEN intensely mediates the proliferation, invasion and metastasis of mouse breast cancer cells via regulating the PI3K-Akt signaling pathway.